Economic feasibility of hybridyzing forward contracts and warehouse receipt system in Malawi - Mbaso, Marvin (Kansas State University, 2018)
Generally, commodity prices immediately after harvest tend to be low because of supply glut and rise over time away from harvest as supply shrinks and demand remains virtually unchanged. Unfortunately, because many Malawian farmers do not have effective storage, they do not have any commodity for sale when prices are high. To help improve the income Malawian farmers may generate from their activities, this thesis explored the feasibility of hybridizing the two forms of price risk management systems in Malawi to minimize their individual weaknesses and enhance their collective benefits. The two risk management systems are forward contracts and warehouse receipt systems. Forward contracts allow farmers and their buyers to agree on a future delivery date and commodity price. On the agreed date, the farmer delivers the commodity and receives the agreed price. It allows farmers to pass downward price risk to buyers and guarantees a fixed price. As private transactions, forward contracts are not regulated by the Government, and present opportunism and enforcement challenges. Warehouse Receipt System (WRS) enables farmers to deposit their crop in the care of a warehouse operator and sell the crop when and where they choose. Farmers, therefore, incur both upside and downside price movement but avoid some of the opportunism and enforcement challenges presented by forward contracts. The thesis explored the net benefits of developing a hybrid system that allow forward contracts with warehouse receipt enforcement mechanisms. Thus, farmers are guaranteed a minimum price at some future date and the deposited commodity is used as the security supporting the guaranteed minimum price. The buyer also deposits a performance bond as commitment to purchase the commodity. The costs associated with these transactions are real and could affect participation. The thesis provides a process for assessing these transaction costs and incorporating them into the effectiveness of forward contracts, warehouse receipt systems and the hybrid program. The mathematical model example has proved that the hybrid system guarantees a fixed margin to the farmer over and above the harvest price and WRS cost as opposed to fluctuating margins under WRS alone. The thesis has identified three factors that can lead to the successful implementation of this hybrid system in Malawi and they include: the availability of the warehouse receipt bill, reliable warehouse certification which is done by AHCX and ACE on third party warehouse operators; and the availability of performance guarantee assuring that the quantities and quality of goods match those specified by the warehouse receipt. The thesis has also identified two factors that could hinder a successful implementation of this hybrid program and they include: first, low scale of warehousing operations under WRS which could deny most farmers a chance to access and benefit from this hybrid sytem and the commodity exchanges may not benefit from the economies of scale provided by large volumes of commodities produced in rural areas. Second, the absence of a harmonized national grading standard which possess a challenge when engaging in international trade. Finally, the thesis has made three recommendations for the successful implementation of the hybrid program as follows: Taking the system close to the producers to mitigate potentially high transportation costs; educating and selling the system to the stakeholders to increase adoption rate; and push for the implementation of national standardized grading regulations.
Keywords: Malawi; Warehouse receipts; Supply chain; Forward contract